The evaluation expression of non-coding RNAs in response to HSV-G47∆ oncolytic virus infection in glioblastoma multiforme cancer stem cells - Vazifehmand, Reza; Ali, Dhuha Saeed; Othman, Zulkefley; Chau, De Ming; Stanslas, Johnson; Shafa, Mehdi; Sekawi, Zamberi (Springer, 2022)
Glioblastoma multiforme is the most aggressive astrocytes brain tumor. Glioblastoma cancer stem cells and hypoxia conditions are well-known major obstacles in treatment. Studies have revealed that non-coding RNAs serve a critical role in glioblastoma progression, invasion, and resistance to chemo-radiotherapy. The present study examined the expression levels of microRNAs (in normoxic condition) and long non-coding RNAs (in normoxic and hypoxic conditions) in glioblastoma stem cells treated with the HSV-G47∆. The expression levels of 43 miRNAs and 8 lncRNAs isolated from U251-GBM-CSCs were analyzed using a miRCURY LNA custom PCR array and a quantitative PCR assay, respectively. The data revealed that out of 43 miRNAs that only were checked in normoxic condition, the only 8 miRNAs, including miR-7-1, miR-let-7b, miR-130a, miR-137, miR-200b, miR-221, miR-222, and miR-874, were markedly upregulated. The expression levels of lncRNAs, including LEF1 antisense RNA 1 (LEF1-AS1), metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), long intergenic non-protein coding RNA 470 (LINC00470), tumor suppressor candidate 7 (TUSC7), HOX transcript antisense RNA (HOTAIR), nuclear paraspeckle assembly transcript 1 (NEAT1), and X inactive specific transcript (XIST), were markedly downregulated in the hypoxic microenvironment, and H19-imprinted maternally expressed transcript (H19) was not observed to be dysregulated in this environment. Under normoxic conditions, LEF1-AS1, MALAT1, LINC00470, H19, HOTAIR, NEAT1, and XIST were downregulated and TUSC7 was not targeted by HSV-G47∆. Overall, the present data shows HSVG47Δ treatment deregulates non-coding RNA expression in GBM-CSC tumor microenvironments.